The Development of a Short-Distance Running Learning Model Based on Colorful Balls Run Games for Phase C Students - Prabowo, Andika; Raibowo, Septian; Bogy Restu Ilahi; Syafrial; yarmani; Meliana; Sugihartono, Tono; Dian Pujianto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to develop a short-distance running learning model based on colorful balls run games for phase C students at elementary school 106 Bengkulu City. This research is a type of Research and Development (R&D) employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The method used is descriptive qualitative. The research population consisted of phase C students at elementary school 106 Bengkulu City, with the sampling technique using total sampling. The research instruments included observation, interviews, questionnaires, and documentation. Based on the validation results, material experts obtained a score of 92% and media experts obtained 88%, both categorized as "very feasible." The small group trial involving 10 students resulted in an average percentage of 79%, categorized as "feasible," while the large group trial involving 40 students achieved an average percentage of 91%, categorized as "very feasible." Based on these findings, it can be concluded that the short-distance running learning model based on colorful balls run games is feasible to be used as a learning model for phase C students at elementary school 106 Bengkulu City.